Techniqes for language acquisition - Bovda, Olena; Nifaka, Tetiana; Бовда, Олена; Ніфака, Тетяна (Східноєвропейський національний університет ім. Лесі Українки, 2015)
The article explores the notion of technique in teaching foreign languages. It is defined as a simple methodical act which provides the realization of the teacher’s educational objective in class. The term is claimed to entail activity, task and exercise. Activity is a broader term, with task applying to a separable element of a lesson, which is primarily geared to practicing language presented, usually involving students working with each other, and which has a specific goal. The classification of the activities depends on the following factors: 1) degree of teacher’s control; 2) categories of use; 3) main types of interaction activities; 4) practice and communicative activities. Their activity types are specified. Task is treated as the basic unit of action. Some distinctions have been drawn between exercises (focused on noticing and developing aspects of the form of language) and tasks (focused on integrated use of language). To develop accuracy and fluency in communicative competence both of them are recommended. The most frequently used way of categorizing tasks is stated to be according to four macro -skills, six activity-types and higher order thinking skills. Tasks characteristics (information structure, recycling, convergence) are given.Розглядається поняття «прийом», раціональне використання якого в процесі формування комунікативної компетенції студентів не викликає сумніву. Прийом визначається як елементарний методичний вчинок, що забезпечує успішну реалізацію конкретної практичної мети на занятті. Він характеризується комплексністю, компонентами якого виступають діяльнісне завдання, завдання, вправа. Діяльнісне завдання включає комунікативну мету, проблемно-пізнавальну та проблемно-методичну задачі, розв’язання яких здійснюється за допомогою завдань та вправ. Класифікація діяльнісних завдань продиктована такими факторами: 1) ступінь контролю викладача; 2) категорії використання; 3) головні типи інтерактивної діяльності; 4) практикування та комунікативна діяльність. Окреслено типи діяльнісних завдань. Завдання розглядається як основний компонент дії. Визначено відмінності між завданням та вправою. Під час виконання першого увага концентрується на змісті висловлювання, другої – на його формі. Критеріями для типології вправ є: основні чотири вміння; шість видів діяльності та розумові вміння. Встановлено основні ознаки (інформаційна структура, переробка, конвергенція) вправ.
Прийоми у навчанні іноземних мов
Keywords: technique; teaching; foreign language; activity; task; exercise; communicative competence; characteristic; прийом; викладання; іноземна мова; діяльнісне завдання; завдання; вправа; комунікативна компетенція; ознака